2020
DOI: 10.1042/bcj20200346
|View full text |Cite
|
Sign up to set email alerts
|

Phospholamban and sarcolipin prevent thermal inactivation of sarco(endo)plasmic reticulum Ca2+-ATPases

Abstract: Na+-K+-ATPase frommice lacking the γ subunit exhibits decreased thermal stability. Phospholamban (PLN) and sarcolipin (SLN) regulate sarco(endo)plasmic reticulum Ca2+-ATPases (SERCAs) with properties similar to the γ subunit, through physical interactions with SERCAs. Here, we tested the hypothesis that PLN and SLN may protect against thermal inactivation of SERCAs. HEK-293 cells were co-transfected with different combinations of cDNAs encoding SERCA2a, PLN, a PLN mutant (N34A) that cannot bind to SERCA2a, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 89 publications
2
7
0
Order By: Relevance
“…Further investigation showed no changes in SERCA2a content or SERCA2a T‐nitration, though this was not due to a lack of total protein nitration. Like SLN, PLN has previously been demonstrated to have a protective effect on SERCA (Fu et al, 2020), and here we show that the LV has much more PLN content relative to soleus, which could be conferring cytotoxic protection. Notably, previous studies have shown that PLN is in fact expressed in the soleus (Braun, Geromella, et al, 2021; Fajardo et al, 2017), and we believe the lack of signal in the soleus speaks to the relative abundance of PLN in the LV compared to the soleus, which not only masks detection in the soleus but may also be preventing T‐nitration and oxidative damage to SERCA2a in the LV.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Further investigation showed no changes in SERCA2a content or SERCA2a T‐nitration, though this was not due to a lack of total protein nitration. Like SLN, PLN has previously been demonstrated to have a protective effect on SERCA (Fu et al, 2020), and here we show that the LV has much more PLN content relative to soleus, which could be conferring cytotoxic protection. Notably, previous studies have shown that PLN is in fact expressed in the soleus (Braun, Geromella, et al, 2021; Fajardo et al, 2017), and we believe the lack of signal in the soleus speaks to the relative abundance of PLN in the LV compared to the soleus, which not only masks detection in the soleus but may also be preventing T‐nitration and oxidative damage to SERCA2a in the LV.…”
Section: Discussionsupporting
confidence: 71%
“…The reduction in Ca 2+ affinity seen in the soleus of Sod 2 +/− mice compared to WT may be partly due to the increase in SLN content, a well‐studied SERCA regulator that can reduce SERCA’s affinity for Ca 2+ (Asahi et al, 2002; Babu et al, 2007; Rathod et al, 2021), in Sod 2 +/− mice compared to WT. Despite not observing a statistically significant increase in SLN in soleus muscles from Sod2 +/− mice, it is worth noting that SLN has been shown to play a protective role for SERCA, preventing thermal inactivation of the pump (Fu et al, 2020). Furthermore, SLN is upregulated in various models of muscle wasting including spaceflight (Braun, Geromella, et al, 2021) and muscular dystrophy (Fajardo et al, 2018; Schneider et al, 2013)—both of which also demonstrate increases in nitrotyrosine (Braun, Geromella, et al, 2021; Cleverdon et al, 2021; Gehrig et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we measured total protein nitrosylation and tyrosine nitration in the gastrocnemius to determine whether elevated RONS could contribute to the observed SR Ca 2+ handling dysfunction in the D2 mdx muscle. SERCA is susceptible to RONS damage and RONS are known to be high in DMD, and therefore, it is plausible that RONS modifications could be contributing to the changes in protein function we see (15,(30)(31)(32)(33)(34). Our results show that excessive and irreversible (detection under reducing conditions) RONS modifications may be impairing function of the SERCA pump.…”
Section: Discussionsupporting
confidence: 49%
“…One potential factor may be elevated oxidative/nitrosative stress. SERCA is susceptible to RONS damage and RONS are known to be high in DMD, and therefore, it is plausible that RONS modifications could be contributing to the changes in SERCA function (15,(30)(31)(32)(33)(34). Our results of elevated total protein nitrosylation and tyrosine nitration under reducing conditions are suggestive of irreversible RONS modifications that may be impairing the SERCA pump.…”
Section: Discussionmentioning
confidence: 59%
“…Several studies have also noted increased oxidation and nitration of SERCA in aged skeletal muscle [ 155 , 214 , 219 ], which we have shown results in the loss of redox control of SERCA activity and expression [ 220 ]. However, our work showing that several SERCA-binding proteins, including heat shock protein 70, PLN, and SLN, can protect SERCA structure and function during cellular stress [ 152 , 159 , 221 ], suggests that these SERCA-binding proteins may play a crucial role in protecting cellular Ca 2+ homeostasis and preserving cardiac and skeletal muscle function under conditions of chronic oxidative stress and disease.…”
Section: Dysregulation Of Ca 2+ Transport In Heart...mentioning
confidence: 99%